2018
DOI: 10.1097/spc.0000000000000380
|View full text |Cite
|
Sign up to set email alerts
|

Understanding sex differences in the regulation of cancer-induced muscle wasting

Abstract: Females and males have unique characteristics that effect skeletal muscle's microenvironment and intrinsic signaling. These differences provide a strong rationale for distinct causes for cancer cachexia development and treatment in males and females.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
60
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(65 citation statements)
references
References 136 publications
(223 reference statements)
5
60
0
Order By: Relevance
“…Our results are consistent with the literature; men are at greater risk, and reasons for this are not fully understood. Possible explanations may be related to sex differences associated with metabolic changes (eg, inflammation) and endocrine dysfunction, which were not collected in the current study . Collectively, these results show that the population is rife with features of cancer‐associated malnutrition (eg, weight loss, reduced food intake), including profound skeletal muscle depletion and fatty infiltration of the muscle, all of which are significantly and independently associated with mortality.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Our results are consistent with the literature; men are at greater risk, and reasons for this are not fully understood. Possible explanations may be related to sex differences associated with metabolic changes (eg, inflammation) and endocrine dysfunction, which were not collected in the current study . Collectively, these results show that the population is rife with features of cancer‐associated malnutrition (eg, weight loss, reduced food intake), including profound skeletal muscle depletion and fatty infiltration of the muscle, all of which are significantly and independently associated with mortality.…”
Section: Discussionmentioning
confidence: 60%
“…Possible explanations may be related to sex differences associated with metabolic changes (eg, inflammation) and endocrine dysfunction, which were not collected in the current study. 25 Collectively, these results show that the population is rife with features of cancerassociated malnutrition (eg, weight loss, reduced food intake), including profound skeletal muscle depletion and fatty infiltration of the muscle, all of which are significantly and independently associated with mortality. As a result, there is interest in determining whether currently existing nutrition screening tools can reveal any facets of body composition that place patients at greater risk for adverse outcomes; however, this seems unlikely, based on current findings.…”
Section: Discussionmentioning
confidence: 85%
“…In their study, the males had clear muscle mass loss at the end of life, which was not observed in females. Various hormones, cytokines, and the immune system are associated with cachexia progression and muscle depletion [37,38] and are considered vital factors that cause sex differences. Elucidation of the mechanism of the sex difference is one of the keys to measures for muscle depletion and requires further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been suggested that there are sex differences in both how cachexia develops and in the severity of the loss of muscle mass and function (Montalvo, Counts, & Carson, 2018), but few studies have directly addressed these sex differences. Female patients and rodents with cancer appear to benefit from the anti-inflammatory effects of estrogen (Hetzler et al, 2015(Hetzler et al, , 2017Koo et al, 2008), which corresponds with data indicating that male cancer patients lost more body weight, muscle mass and have higher rates of mortality compared with their female counterparts (Baracos, Reiman, Mourtzakis, Gioulbasanis, & Antoun, 2010;Hendifar et al, 2009).…”
mentioning
confidence: 99%